Exploring Prodrug Approaches for Albitiazolium and its Analogues - Peyrottes, Suzanne; Caldarelli, Sergio; Wein, Sharon; Perigaud, Christian; Vial, Henri (Current Topics in Medicinal Chemistry, 2014)
Choline analogues such as bis-thiazolium salts are thought to inhibit choline transport into Plasmodiuminfected erythrocytes, thus preventing parasite PC biosynthesis, and also to interact with plasmodial haemoglobin degradation in the food vacuole. This new and multiple mode of action is a major asset of these new class of antimalarials, as they could help delay resistance development. We synthesized and designed various sets of analogues, notably prodrugs, since the oral bioavailability of bis-thiazolium salts is relatively low. The chemistry underlying this synthesis relies on inexpensive and readily available starting materials and is straightforward. This is essential since the ultimate objective is to obtain affordable and orally available drugs for uncomplicated malaria treatment.
Keywords: thiazolium salts